The virtuous woman and the holy nation: Femininity in the context of Pentecostal Christianity in Vanuatu. (28th April 2016) - Eriksen, Annelin
Abstract : In this paper I connect an anthropology of Christianity to an anthropology of the body and an anthropology of the nation. I try to achieve this by looking at changing notions of femininity in the Pentecostal context of Vanuatu. I do this on two different levels; on the one hand I show how the meaning of womanhood is changed in what I call the 'pentecostalised' neighborhoods of the capital Port Vila, and on the other I show how the household and the nation become contexts into which this new notion of femininity is played. Thus, in the first part of the paper I look at the ways in which Pentecostal Christianity change the meaning of gender, whereas in the second part of the paper I look at how this new form of gendered meaning has relevance for our understanding of wider social contexts.